ARG2 single-nucleotide polymorphism rs3742879 affects plasma arginase 2 levels, nitric oxide formation and antihypertensive therapy response in preeclampsia - Luizon, Marcelo R.; Pinto-Souza, Caroline C. [UNESP]; Coeli-Lacchini, Fernanda; Lacchini, Riccardo; Cavalli, Ricardo C.; Sandrim, Valeria C. [UNESP] (Taylor & Francis, 2022)
Aim: This work examined whether ARG1 (rs2781659, rs2781667, rs2246012 and rs17599586) and ARG2 (rs3742879 and rs10483801) single-nucleotide polymorphisms (SNPs) are associated with antihypertensive therapy responsiveness in preeclampsia (PE) and their effects on arginase isoforms and nitrite concentrations in responsive and nonresponsive patients. Methods: SNP genotypes were determined by TaqMan assays. Plasma arginase levels were measured by ELISA and nitrite concentrations were measured using an ozone-based chemiluminescence assay. Results: The G allele for ARG2 rs3742879 (A>G) was less frequent in nonresponsive compared with responsive patients (15.5% vs 24.7%, respectively) and the G carriers of the nonresponsive subgroup had lower arginase 2 (9.2 ± 7.5 ng/ml vs 19.1 ± 17.3 ng/ml) and higher nitrite concentrations (110.2 ± 52.8 nM vs 78.5 ± 37.9 nM) than carriers of the AA genotype (all p < 0.05). Conclusion: ARG2 SNP rs3742879 is associated with diminished arginase 2 levels and increased nitric oxide formation in nonresponsive PE patients.
Keywords: ARG2; arginase 2; genetic polymorphisms; hypertension; nitric oxide; nitrite; pharmacogenetics; preeclampsia